Электропроводящие покрытия для защиты от электрокоррозии: обоснование конструкции защиты и требований к покрытию - Плугин, А. А. (НТУ "ХПИ", 2013)
В статье представлен новый способ защиты бетонных, железобетонных, каменных конструкций и сооружений от электрокоррозии. Разработана конструкция способа защиты и требования к ее основному элементу - электропроводящему защитному покрытию. Определены конструкции и сооружения, для которых данный способ защиты является наиболее актуальным.

The paper presents a new method for protecting concrete, reinforced concrete and masonry constructions from electric corrosion. There are worked out the design of method for protection and technical requirements to its basic element - an electrically conductive covering. It is presented a list of structures and facilities for which this method of protection is the most actual.
Keywords: железобетон; конструкции каменные; сопротивление электрическое; сопротивление удельное; electrically conductive coating; electric corrosion; protection; concrete; reinforced concrete; masonry construction; electrical resistivity